Tinjauan Etis Situasional dalam Formulasi Keputusan Insentif Bagi Community Worker Bank Sampah PKK di Sidoarjo - Rr. Febrina Prima Sari (Tanzhim: Jurnal Dakwah Terprogram, 2026)
Situational Ethical Decision: Formulating Incentive Policies For PKK Waste Bank Community Workers In Sidoarjo. Ethical specificity regarding decisions of good or moral wrong within situational contexts is essential for organizational governance. Organizations that pursue mission-aligned objectives under Islamic values may encounter difficulties when relying solely on general codes of ethics to address context-specific ethical dilemmas. The failure of managers within such organizations to apply a balanced ethical framework in resolving particular dilemmas can increase the risk of disharmony, diminished employee motivation, and trust issues. The PKK Waste Bank of Housing X in Sidoarjo operates with environmental da’wah objectives, incorporating education on waste sorting and savings to minimize environmental residues while simultaneously supporting the economic empowerment of the community. The chairperson of PKK confronts an ethical dilemma in formulating policy amid social welfare considerations, despite the fact that community workers exert substantial effort within a relatively modest funding envelope. This phenomenon necessitates problem-solving founded on a theory of decision-making in applied ethics, which elucidates the considerations involved in formulating applied ethical decisions and delineates the stages required to produce a balanced ethical decision formulation for multiple stakeholders within a specific context. The present study offers a qualitative account of the process by which an ethical policy formulation is established, focusing on a case study of a situational dilemma encountered by PKK’s waste bank. Data were collected through semi-structured interviews with organizational administrators and participant observation. The study yields an incentive framework consisting of an annual monetary payment, calculated from net income after deducting the bank’s idle cash (IDR 200,000), with 10% allocated to PKK funds and 90% directed to community workers